2013
DOI: 10.4236/psych.2013.43a032
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Ownership: Different Effects on Explicit Ratings and Implicit Responses

Abstract: This study is based on the idea that emotion-related processing happens on various different levels. Common methods that are used to measure different aspects of emotion-related processing exhibit specific sensitivities to one or the other of these separate processing levels. Here, the hypothesis was tested that explicit and implicit measures of emotion-related processing are differently influenced by self-referenced versus unreferenced emotion. The explicit measure was self reported valence and the implicit m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…Said differently, it is possible that actively paying attention to ones own emotions rather than simply observing emotional events can have a regulatory influence, impeding the formation of a stronger negative emotional state. Walla et al (2013a) found that self referenced negative emotion images were rated more negative that un-referenced negative images and self-referenced positive images were rated more positive than un-referenced positive images. In their study, startle responses were enhanced as a result of self reference regardless of emotion valence.…”
Section: Discussionmentioning
confidence: 92%
“…Said differently, it is possible that actively paying attention to ones own emotions rather than simply observing emotional events can have a regulatory influence, impeding the formation of a stronger negative emotional state. Walla et al (2013a) found that self referenced negative emotion images were rated more negative that un-referenced negative images and self-referenced positive images were rated more positive than un-referenced positive images. In their study, startle responses were enhanced as a result of self reference regardless of emotion valence.…”
Section: Discussionmentioning
confidence: 92%
“…This is an important issue, since there is evidence pointing to relatively modest levels of convergence between subjective, behavioral and physiological findings, together with reports of dissociations between these response systems (for a review see Mauss and Robinson, 2009 ). These data has led some authors to recommend the use of multiple measures that can capture different aspects of the emotional response (Mauss et al, 2005 ; Lyons et al, 2013 ; Walla et al, 2013 ), while others have suggested efforts to improve the way self-reports are used, in order to develop better first person methods (Nielsen and Kaszniak, 2007 ). However, thus far the literature on emotional changes after brain damage has by and large failed to consider the subjective experience of emotions, mostly focusing on individuals' ability to perceive or express feelings [see introduction].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that events or situations that are appraised as relevant and significant to one’s goals and wellbeing induce emotions more effectively than irrelevant ones ( Freeman et al, 2005 ; Lazarus, 1991 ). For instance, the emotional valence of visual scenes is significantly enhanced when they are paired with short sentences inducing self-reference (e.g., “ this dog will attack you ” written underneath the image of an aggressive dog: Walla et al, 2013 ). Simulations are also more likely to affect the user’s emotional state when they have a higher degree of personal relevance ( Freeman et al, 2005 ; Hoorn, Konijn & Van der Veer, 2003 ).…”
Section: Introductionmentioning
confidence: 99%